Novel polymer electrolyte based on cob-web electrospun multi component polymer blend of polyacrylonitrile/poly(methyl methacrylate)/polystyrene for lithium ion batteries : preparation and electrochemical characterization - Srinivasan, Madhavi (2012)
The aim of the present work is to prepare a novel polymer electrolyte (PE) based on multi component polymer blend of polyacrylonitrile (PAN), poly(methyl methacrylate) (PMMA) and polystyrene (PS) with varying compositions by electrospinning. Structural characterization is carried out using X-ray diffraction (XRD). The thermal and crystalline properties of the blend are studied by thermo-gravimetric analysis (TGA) and differential scanning calorimetry (DSC), respectively. Morphology of the membrane is examined by field emission scanning electron microscope (FE-SEM). The voids and cavities generated by the interlaying of the fibers are effectively utilized for the preparation of PE by loading with lithium hexafluorophosphate (LiPF6) dissolved in ethylene carbonate (EC)/diethyl carbonate (DEC). The ionic conductivity of the polymer blend electrolyte is studied by varying the PMMA and PS content in the PAN matrix. The blend polymer electrolyte shows ionic conductivity of about 3.9 × 10(−3) S cm(−1). The performance evaluation in coin cells show good charge–discharge properties and stable cycle performance under the test conditions. The result shows that the prepared polymer blend electrolytes are promising materials for lithium ion batteries.